Hubungan Dukungan Suami Dengan Kejadian Post Partum Blues Di Wilayah Perkotaan - Samria Samria; Indah Haerunnisa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
Post partum is the period after giving birth to the recovery of the uterus and female organs which is generally accompanied by the discharge of postpartum blood.The length of the post partum period is around 6-8 weeks. In addition to body changes, the post partum period will also result in changes in psychological conditions. Research Objectives To determine the relationship between husband's support and the incidence of post partum blues in urban areas. The research method used was analytic survey research design and cross sectional approach. The number of samples is 40 people. Sampling using a support questionnaire. The results of the analysis of the relationship between the two variables above by using the chi-square statistical test obtained the significance of the relationship between the two variables is p = 0.000, p = 0.000 <α 0.05, this means that Ha is accepted and Ho is rejected, so there is a relationship. husband's support with the incidence of post partum blues in urban areas. Suggestion Can provide health education and education to postpartum mothers by presenting a husband as a companion to the mother so that the risk of post partum blues can be better prevented.